Rancang Bangun Aplikasi Pembelajaran Kamus Rumus Matematika Tingkat SMA Berbasis Android: Design and Build a Formula Dictionary Learning Application Android-Based High School Level Mathematics - Marlinda Sanglise; Ivana Wardania (JISTECH: Journal of Information Science and Technology, 2018)
Today the community has switched to digital media, this development has triggered thegeneral public to use something that is easy to use and can be accessed anywhere andanytime with a very high level of mobility. Mobile-based applications have become partof life even in the field of education today. Mathematics is a subject that is consideredcomplicated especially in remembering mathematical formulas so that an application isneeded that can help find mathematical formulas quickly. Purpose of making learningapplications android-based high school Mathematics formulas is to convertMathematical formula books into digital form so that they can be an alternative mediabesides printed books. Research applications are built using android studio, and usethe Java language that runs into XML as a display. This research was also conductedusing methods namely analysis, designing, implementation, and testing. The results ofthis study are the formation of an android-based high school level MathematicsFormula learning application. From the test results, 56% agree with the application thatwas made and can make learning activities more enjoyable because they are easy tounderstand.